Marjinalisasi Petani Mempertahankan Sumber Penghidupan Akibat Pembangunan Bandara Internasional di Yogyakarta, Indonesia - Napsiah Napsiah; Astri Hanjarwati (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
The development of the Yogyakarta International Airport aims to push the community’s economy. However, in practice, it faces failure. The land expansion needed for the airport operation has caused a loss of the source of income for the farmers nearby and the moving of their residences. Meanwhile, no working sites are accessible to the farmers where they are relocated. This study reveals the marginalization of farmers in maintaining their source of livelihood around the construction site of the Yogyakarta International Airport. This study uses interview methods, indirect observation, and document studies. The findings in this study are: the farmers experience marginalization in accessing work, land, and capital. They then experience uncertainty in income and loss of creativity as farmers. Therefore, the development of the airport has marginalized the farmers. This is an indicator of the failure of development goals. Therefore, a policy is needed to provide agricultural land for farmers to manage and get a source of livelihood.